Optical Face-Contour Analysis - O. F-C. A - V. Retnasamy; Prabakaran, Prof. Madya Dr.; Zaliman, Sauli, Kapt. Prof. Madya; Sazali, Yaacob, Prof. Dr.; W. M. W. Nor Haimi; S. Taniselass; N. Ramli; M. H. A. Aziz; R. M. Hatta; B. Man; Saif, Ala'eddin A. (Malaysian Invention and Design Society (MINDS), 2010)
21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 was held at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.